Wildflower field guide - Campbell, Carol Anne (New York : Sommerville House Book, 1993)
Describes how to identify, pick, and preserve twenty-eight flowers common to North American back yards, parks, fields, and meadows.
Keywords: Wild flowers -- Collection and preservation -- Juvenile literature; Wild flowers -- Identification -- Juvenile literature